2015
DOI: 10.1080/14680629.2015.1091376
|View full text |Cite
|
Sign up to set email alerts
|

The effects of using different bitumen modifiers and hydrated lime together on the properties of hot mix asphalts

Abstract: In this study, the effects of styrene-butadiene-styrene (SBS), American gilsonite (AG) and Iranian gilsonite (IG) usage in bitumen modification, and hydrated lime usage in mixture modification on the performance of hot mix asphalts (HMAs) were investigated. For bitumen modification, 4.0% SBS, 11.0% AG and 10.0% IG were used with respect to bitumen weight. Hydrated lime was used as filler in proportion of 2% with respect to aggregate weight. It was determined that the high temperature properties of bituminous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In a previous study conducted, the effects of additives and lime use on rutting formation were investigated by using the wheel tracking test method [23]. The results obtained in this study were found to be similar to the results of the previous study, indicating that the most effective additive in terms of resistance to permanent deformation is AG, while the least effective one is SBS and lime use is not as effective as the additive use.…”
Section: Results Of Dynamic Creep Testsupporting
confidence: 80%
See 2 more Smart Citations
“…In a previous study conducted, the effects of additives and lime use on rutting formation were investigated by using the wheel tracking test method [23]. The results obtained in this study were found to be similar to the results of the previous study, indicating that the most effective additive in terms of resistance to permanent deformation is AG, while the least effective one is SBS and lime use is not as effective as the additive use.…”
Section: Results Of Dynamic Creep Testsupporting
confidence: 80%
“…DSR and bending beam rheometer (BBR) test results of neat and modified bitumens are presented in Table 1. As seen in Table 2, the modified bitumen performance level is PG 70-22, which meets the necessary level for the area of application [23]. Viscosity values were increased due to use of additives, which in turn increased the mixing and compaction temperatures.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…The application of modified bitumen can reduce stripping. In addition to impacts on the bond between aggregate and bitumen, anti-stripping materials can change the hardness and rutting resistance and increase or decrease the propagation of cracks [5]. On the other hand, the image processing of asphalt mixture specimens was first conducted for a project entitled "thermography image processing in an asphalt core" in 1993 at the University of Southern California.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise cracking may cause very serious problems, such as poor ride quality, reduced service life, and high maintenance costs [5]. Polymeric materials can be used as modifiers in bitumen and hot mix asphalt (HMA) mixtures so that a wider performance range can be achieved [6][7][8]. When plastomers are incorporated into bitumen, the resultant structure is a rigid three dimensional network that resists deformation.…”
Section: Introductionmentioning
confidence: 99%